Reliability and validity of three isometric back extensor strength assessments with different test postures. Issue 2 (October 2020) - Yang, Sen; Wu, Wenjie; Zhang, Chengmin; Wang, Donggui; Chen, Can; Tang, Yong; Li, Kai; Xu, Jianzhong; Luo, Fei
Objective: To compare the test-retest reliability and validity of three simple maximal isometric back extensor strength (BES) assessment protocols with different test postures, and to recommend an optimal clinical protocol to quantify BES. Methods: Asymptomatic adults, aged over 45 years, were assessed for maximal isometric BES using external fixation of dynamometers, with the subject in standing, prone and sitting positions, respectively. Measurements were repeated at a one-week interval to examine test-retest reliability. Validation was performed by comparing with results obtained from isokinetic dynamometer assessments. Results: Out of a total of 60 included participants, intra-class correlation coefficients (ICC) were 0.92, 0.93 and 0.90 in standing, prone and sitting positions, respectively. Correlation analyses revealed acceptable convergent validity in the standing and prone position (r = 0.50 and 0.54, respectively), whereas tests conducted in the sitting position showed a relatively low validity (r = 0.32). Among the three protocols, measurement error was lowest in the prone position. Conclusions: Maximal isometric BES assessment in the prone position was shown to be the most reliable and valid protocol, and may be considered the preferred option for assessing BES in clinical practice.